Przywództwo w zarządzaniu organizacją - Tkaczyk, Stanisław (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The role of leadership and a leader in the management of an organization in accordance with the quality principles are presented. Different definitions of the leadership and a leader are quoted, among others a definition set out for the purpose of the competition named Polska Nagroda Jakości (Polish Award for Quality Management). The continuous process of the management improvement of an organization is described, including the improvement of its effectiveness. Development trends of contemporary organizations are presented. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1177, s. 158-166